A study on typhoon disaster risk zoning in Zhejiang coastal areas - WANG Zhenguo; KANG Lili; LI Te; JIANG Kaihua; LIU Chao; HOU Hui (Zhejiang dianli, 2024)
Zhejiang， as a crucial coastal province in China， deems the delineation of risk zones in its power system imperative for minimizing losses caused by typhoon disasters. Initially， the paper leverages historical data to comprehensively analyze meteorological features of typhoons in the Zhejiang coastal areas， focusing on aspects such as landing point distribution， path characteristics， temporal patterns， wind speed attributes， and precipitation features. Subsequently， an analysis of typhoon disaster characteristics in the Zhejiang power system is conducted. This entails examining the distribution of fault points in the transmission system， the relationship between the substation system and typhoon landing points， and the distribution of power outage percentages in the distribution system. Finally， utilizing historical data from both Zhejiang’s typhoon meteorology and power system， the paper creates a map outlining the risk zones for typhoon disasters. This includes a detailed delineation of high-risk areas for tower collapses， areas prone to wind deviations， and regions with high geological disaster risks. The analysis results aim to support risk assessment and response measures for typhoon disasters across various levels of the power grid.